The use of swear words in twitter / Devi Rajeswari Sivaraj - Devi Rajeswari, Sivaraj (2016)
The f-word is a popular swear word used on social media and it is used in different forms and functions. This study investigates the uses of the f-word on a social media platform, Twitter. This study was carried out to address the following questions: (1) What are the syntactic forms of the f-word found on Twitter? (2) What are the functions of the f-word on Twitter? (3) What are the differences and similarities of the findings of this study with McEnery and Xiao’s (2004) study of the f-word in the British National Corpus (BNC)? The data comprised a corpus of 12,000-word from Twitter. Holster’s (2005) classification was used in this study to examine the syntactic forms of the f-word. This study employed McEnery et al. (2000) and Ljung (2011) typologies to analyze the functions of the f-word. The findings showed that the f-word is highly used as a verb, and it is used mainly to curse on Twitter. The results obtained in this study show some similarities to McEnery and Xiao’s (2004 findings in the BNC.